2022
DOI: 10.1088/1361-6501/ac82db
|View full text |Cite
|
Sign up to set email alerts
|

Detection method of obstacles in the dangerous area of electric locomotive driving based on MSE-YOLOv4-Tiny

Abstract: Aiming at the problems of error warning, low detection efficiency, and inability to meet the requirements of lightweight deployment in current track obstacle detection algorithms based on computer vision, the detection method of obstacles in the dangerous area of electric locomotive driving based on improved YOLOV4-Tiny (MSE-YOLOV4-Tiny) was proposed. The obstacle image dataset was constructed to provide a testing environment for various target detection algorithms. The method of perspective transformation, sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Using a nonlinear method, the size of the receptive field can automatically change according to the incentive factors, which can automatically adjust the size of the receptive field with the difference of input scale. SKNet network consists of multiple SK convolution units stacked, in which The SK convolution operation is divided into three parts: split, fuse, and select, as shown in Figure 3 42 …”
Section: Related Research Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a nonlinear method, the size of the receptive field can automatically change according to the incentive factors, which can automatically adjust the size of the receptive field with the difference of input scale. SKNet network consists of multiple SK convolution units stacked, in which The SK convolution operation is divided into three parts: split, fuse, and select, as shown in Figure 3 42 …”
Section: Related Research Algorithmsmentioning
confidence: 99%
“…SKNet network consists of multiple SK convolution units stacked, in which The SK convolution operation is divided into three parts: split, fuse, and select, as shown in Figure 3. 42 SKNet convolution is no longer an attention mechanism limited to channel level and space level, but an attention mechanism is applied to convolution cores of different sizes, thus allowing the network to adaptively adjust its structure. Furthermore, SK convolution is also a lightweight plug-and-play module that does not add too much computation to the network while bringing accuracy gains.…”
Section: Sknet Networkmentioning
confidence: 99%
“…It can be observed that the second-order difference of the sequence H i ¢ is independent of i, indicating that the first-order difference of the sequence H i ¢ is an arithmetic sequence. According to equation (18)…”
Section: H D H H H H D H H Dh H H D H H H H V U H D H H H H D H H H H...mentioning
confidence: 99%
“…This approach has several advantages, including lower cost, greater flexibility, mature algorithms, high accuracy, and reliability. As a result, monocular vision systems find wide application in diverse fields, including robot navigation [15][16][17], obstacle distance measurement [18][19][20][21], and pose estimation [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, deep learning object detection algorithms are mainly divided into two categories. Among them, one is onestage detection algorithms based on regression, mainly represented by single shot multibox detector (SSD) [14], you only look once (YOLO) [15,16], and the other is two-stage detection algorithms based on candidate region, mainly represented by Region CNN (RCNN) [17], Faster RCNN [18,19], Mask RCNN [20]. Given the same detection accuracy, one stage detection algorithms are widely used in industries, such as steel quality inspection, battery quality inspection, vehicle inspection, circuit board quality inspection, sawn timber quality inspection, and insulator equipment inspection, due to their advantages of fast speed and low hardware dependency.…”
Section: Introductionmentioning
confidence: 99%